PENINGKATAN LITERASI MASYARAKAT DALAM RANGKA PELESTARIAN EKOSISTEM MANGROVE DI KAWASAN BAGEK KEMBAR, SEKOTONG LOMBOK BARAT - Virgota, Arben; Baiq Farista; Astrini Widiyanti; Ernawati; Lalu Muhammad Aby Dujana; Nurul Hidayati; Nur Indah Julisaniah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The Mangrove Essential Ecosystem Area of Bagek Kembar Sekotong, West Lombok, is a crucial resource supporting both ecological sustainability and the local community’s economy. However, low literacy and insufficient community involvement in conservation remain major obstacles for sustainable management in this area. This community service initiative aims to enhance environmental literacy through the dissemination of research findings and the establishment of a reading center. The methods used include counseling, participatory discussions, and the founding of a reading center involving youth groups, the “Jalan Pulang” sanggar managers, local tourism stakeholders (Pokdarwis), and village officials. The results show active participant engagement in discussions, the emergence of initiatives and questions related to conservation funding and carbon trading opportunities, as well as the establishment of a reading center as a hub for learning and community collaboration. This activity has proven effective in building an environmental literacy network and strengthening community empowerment synergy to support mangrove ecosystem sustainability.